Respuesta :

Answer:

(4,5)

Step-by-step explanation:

Let's solve your system by substitution.

2y=x+6;3x=y+7

Step: Solve2y=x+6for x:

2y=x+6

2y+−x=x+6+−x(Add -x to both sides)

−x+2y=6

−x+2y+−2y=6+−2y(Add -2y to both sides)

−x=−2y+6

−x

−1

=

−2y+6

−1

(Divide both sides by -1)

x=2y−6

Step: Substitute2y−6forxin3x=y+7:

3x=y+7

3(2y−6)=y+7

6y−18=y+7(Simplify both sides of the equation)

6y−18+−y=y+7+−y(Add -y to both sides)

5y−18=7

5y−18+18=7+18(Add 18 to both sides)

5y=25

5y

5

=

25

5

(Divide both sides by 5)

y=5

Step: Substitute 5 for y in x=2y−6:

x=2y−6

x=(2)(5)−6

x=4(Simplify both sides of the equation)